Effect of Botanical Extracts on Late Blight (Phytopthora infestans) and Productivity of Tomato (Solanum esculentum) - T. Choga; E. Ngadze; J. T. Rugare; S. Mabasa; W. Makaza; V. O. Gwatidzo; S. Chikuta; G. Karubanga (International Journal of Agronomy)
Late blight is caused by Phytopthora infestans (Mont.) de Bary which establishes quickly in Solanum esculentum L. (tomato); as a result, it makes the pathogen one of the most devastating plant diseases across the world. The control of late blight is difficult because P. infestans has advanced and complex enzymes and effecter molecules coded by avirulence genes. As such, a study was carried out at the University of Zimbabwe, Department of Plant Production Sciences and Technologies, between August 2018 and May 2019 to evaluate the efficacy of Moringa oleifera Lour. (moringa), Eucalyptus nigra R.T. Baker (gumtree), and Lantana camara L. (sensu lato) (lantana) extracts as biofungicides on late blight development on S. esculentum. The effect of acetone, ethyl acetate, and water extracts of M. oleifera, E. nigra, and L. camara on percent inhibition and radial growth were evaluated in the laboratory. In addition, the efficacy of different extract concentrations of M. oleifera, E. nigra, and L. camara L. on defence enzymes, disease incidence, disease severity, and yield parameters of S. esculentum were assessed in the in vivo experiment. Increasing concentration of the botanical extracts significantly (p≤0.05) reduced radial growth and increased percent inhibition of P. infestans. In addition, increasing botanical extract concentration significantly (p≤0.05) increased peroxidase (PОD), phenylalanine ammonia lyse (PAL), and polyphenol oxidase (PPO) activity. Disease incidence and severity were significantly (p≤0.05) reduced as the concentration of the botanical extracts increased. Similarly, marketable and total yield significantly (p≤0.05) increased with increase in the botanical extract concentration. Gas chromatography mass spectrometry (GCMS) revealed the presence of furfural, 5-methyl-4- (trifluoromethyl) pyrido, dodecanamide, cyclopentasiloxane, and decamethyl. From the research, it can be concluded that M. oleifera ethyl acetate, E. nigra ethyl acetate, and L. camara water extracts contain antifungal compounds and can be used as biofungicides in late blight management.